Sacerdoti ricoverati nel manicomio di Reggio Emilia tra Ottocento e Novecento = Priests admitted to the psychiatric hospital of Reggio Emilia between 19th and 20th century - Paolella, Francesco (Rivista di storia della Chiesa in Italia, 2017)
The paper analyses some cases of catholic priests, admitted to one of the major Italian psychiatric hospitals, San Lazzaro in Reggio Emilia, since 1870 to 1940 approximately. All them were clergymen, some with parish responsibilities, and they came from different regions of north Italy. Studying their case files, we can see they were often poor, lonely and not infrequently alcoholic. The psychiatrists working in San Lazzaro, searching the origin of their mental diseases, focused on their exaggerated studies, their religious doubts and, sometimes, on the bad relationship with their parishioners.